A Novel Naphthoquinone-Coumarin Hybrid That Inhibits BCR-ABL1-STAT5 Oncogenic Pathway and Reduces Survival in Imatinib-Resistant Chronic Myelogenous Leukemia Cells - Martín-Rodríguez, Patricia; Guerra, Borja; Hueso-Falcón, Idaira; Aranda-Tavío, Haidee; Díaz-Chico, Juan; Quintana, José; Estévez, Francisco; Díaz-Chico, Bonifacio; Amesty, Angel; Estévez-Braun, Ana; Fernández-Pérez, Leandro (Frontiers in Pharmacology, 2019)
BCR-ABL1-STAT5 is an oncogenic signaling pathway in Human Chronic Myelogenous Leukemia (CML) and it represents a valid target for anti-CML drug design. Resistance to direct BCR-ABL1 inhibitors is a common clinical issue, so STAT5 inhibition has become an interesting alternative target. In this study, the effects of NPQ-C6, a novel naphtoquinone-coumarin conjugate, were evaluated on human CML-derived K562 cells. Live-Cell Imaging analysis revealed that NPQ-C6 inhibited 2D (IC50AUC = 1.4 ± 0.6µM) growth of CML cells. NPQ-C6 increased sub-G1 and reduced G0/G1 cell cycle phases in a dose- and time-dependent manner. This effect on cell cycle was related to increased levels of apoptotic nuclei, cleavage of caspase-3, -9, and PARP and annexin V-positive cells. NPQ-C6 increased γH2AX, a double-strand DNA break marker. NPQ-C6 showed a wide range of modulatory effects on cell signaling through an early increased phosphorylation of JNK, P38-MAPK and AKT, and decreased phosphorylation of ERK1/2, BCR-ABL1 and STAT5. NPQ-C6 inhibited expression of c-MYC and PYM-1, two target gene products of BCR-ABL1/STAT5 signaling pathway. Cytokine-induced activation of STAT5/STAT3–dependent transcriptional and DNA binding activities were also inhibited by NPQ-C6. Notably, NPQ-C6 maintained its activity on BCR-ABL1/STAT5/c-MYC/PIM-1 oncogenic pathway in imatinib-resistant cells. Molecular modeling suggested BCR-ABL1 and JAK2 proteins as NPQ-C6 targets. In summary, our data show a novel multikinase modulator that might be therapeutically effective in BCR-ABL1-STAT5-related malignancies.